Regular use of traditional analgesics predicts major coronary events: A cohort study - Mikko Haara; Markku Heliövaara; Jari PA Arokoski; Paul Knekt; Pirjo Manninen; et al (Dove Medical Press, 2008)
Mikko Haara1, Markku Heliövaara2, Jari PA Arokoski3, Paul Knekt2, Pirjo Manninen4, Arpo Aromaa2, Antti Reunanen2, Olli Impivaara2, Heikki Kröger51Bone and Cartilage Research Unit (BCRU), University of Kuopio, Kuopio, Finland; 2National Public Health Institute, Helsinki and Turku, Finland; 3Department of Physical and Rehabilitation Medicine, Kuopio University Hospital, Finland; 4Finnish Institute of Occupational Health, Kuopio, Finland; 5Department of Surgery/Orthopaedics and Traumatology, Kuopio University Hospital, Kuopio, FinlandAims: Serious concern has arisen about the cardiovascular safety of selective cyclo-oxygenase-2 (COX-2) inhibitors. However, recent studies have shown that the cardiovascular risks of regular use of traditional analgesics also deserve attention. We investigated the use of traditional analgesics for their prediction of major coronary events during 16 years of follow-up.Methods: A population sample of 8000 Finns aged 30 years and over was invited to a comprehensive health examination in 1978–1980; 7217 (90%) complied, and 4824 of these had no diagnosed cardiovascular disease. The participants filled in a questionnaire eliciting information on the use of analgesics. Record linkage to the National Hospital Discharge Register and the mortality register of the Central Statistical Office of Finland identified 266 major coronary events (myocardial infarctions or coronary deaths) by the end of 1994.Results: The risk of a major coronary event was significantly elevated among those reporting regular use of analgesics at baseline. Compared with nonusers and adjusted for known risk factors for coronary heart disease, the relative risk of an event during the whole follow-up period was 1.51 (95% confidence interval [CI] 1.08–2.10) among regular users of analgesics. The risk was as high as 5.27 (95% CI 2.13–13.11) during the first two years of the follow-up. Thereafter it leveled off.Conclusion: Based on sales statistics almost all analgesics used in Finland at the end of the 1970’s were nonsteroidal antiinflammatory drugs (NSAIDs). Therefore, the increased risk of major coronary events among regular users of analgesics is likely to be due to traditional NSAIDs.Keywords: acute myocardial infarction, coronary heart disease, cohort study, analgesics, pharmacology, risk factors